(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article comprehensively analyzes the causes of tax fraud in the Republic of Uzbekistan in the context of corruption and the level of legal awareness. The study is based on empirical data collected during 2022–2024, reports of international organizations (Transparency International, World Bank, IMF), national statistics and information from state tax authorities. The article identifies institutional, psychological, economic and social factors that cause tax evasion and tax fraud, and their interrelation is scientifically substantiated. The study was conducted based on the Allingham-Sandmo theoretical model, Tax Culture Theory and Social Norm Theory.